Palmatine as an Agent Against Metabolic Syndrome and Its Related Complications: A Review - Ekeuku SO; Pang KL; Chin KY (Dove Medical Press, 2020)
Sophia Ogechi Ekeuku,1 Kok-Lun Pang,1 Kok-Yong Chin1,2 1Department of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Cheras, Kuala Lumpur, Malaysia; 2State Key Laboratory of Oncogenes and Related Genes, Renji-Med X Clinical Stem Cell Research Center, Department of Urology, Ren Ji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of ChinaCorrespondence: Kok-Yong ChinDepartment of Pharmacology, Faculty of Medicine, Universiti Kebangsaan Malaysia, Jalan Yaacob Latif, Bandar Tun Razak, Cheras 56000, Kuala Lumpur, MalaysiaTel +60 3-9145 9573Email chinkokyong@ppukm.ukm.edu.myAbstract: Palmatine is a naturally occurring isoquinoline alkaloid with various pharmacological properties. Given its antioxidant and anti-inflammatory properties, palmatine may be able to impede the effects of metabolic syndrome (MetS) and its related diseases triggered by inflammation and oxidative stress. This review summarises the existing literature about the effects of palmatine supplementation on MetS and its complications. The evidence shows that palmatine could protect against MetS, and cardiovascular diseases, osteoporosis and osteoarthritis, which might be associated with MetS. These protective effects are mediated by the antioxidant and anti-inflammatory properties of palmatine. Although preclinical experiments have demonstrated the efficacy of palmatine against MetS and its related diseases, no human clinical trials have been performed to validate these effects. This research gap should be bridged to validate the efficacy and safety of palmatine supplementation in protecting humans against MetS and its related diseases.Keywords: anti-inflammation, antioxidant, myocardial reperfusion injury, obesity, osteoporosis, osteoarthritis